The molecular structure and vibrational spectra of 1-amino-5-benzoyl-4-phenylpyrimidin-2(1H) by Hartree-Fock and density functional methods - Atalay, Y.; Yakuphanoğlu, Fahrettin; Sekerci, M. (Pergamon-Elsevier Science Ltd, 2006)
The molecular structure and vibrational spectra of 1-amino-5-benzoyl-4-phenylpyrimidin-2(1H) (C17H13N3O2) have been investigated by Hartree-Fock and density functional method using standard B3LYP with 6-31G(d) basis set. The calculated results of the geometric bond lengths and bond angles obtained by using HF and DFT (B3LYP) are in very good agreement with the experimental values. Comparison of the observed fundamental vibrational frequencies of 1-amino-5-benzoyl-4-phenylpyrimidin-2(1H) (C17H13N3O2) and calculated results by density functional B3LYP and Hartree-Fock methods indicate that B3LYP is superior to the scaled Hartree-Fock approach for molecular vibrational problems. (c) 2006 Elsevier B.V.. All rights reserved.
Keywords: 1-amino-5-benzoyl-4-phenylpyrimidin-2(1H); IR spectra; DFT; HF; vibrational assignment; crystal structure